2014
DOI: 10.1007/s11033-014-3591-x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cysteine-rich protein 2 expression in vascular injury and atherosclerosis

Abstract: Vascular smooth muscle cells (VSMCs) of the arterial wall normally display a differentiated and contractile phenotype. In response to arterial injury, VSMCs switch to a synthetic phenotype, contributing to vascular remodeling. Cysteine-rich protein 2 (CRP2) is a cytoskeletal protein expressed in VSMCs and blunts VSMC migration in part by sequestering the scaffolding protein p130Cas at focal adhesions. CRP2 deficiency in mice increases neointima formation following arterial injury. The goal of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Other proteins with increased abundance linked to atherosclerosis were the cysteine and glycine-rich protein 2 (CSRP2), which modulates SMC phenotype and thus influences vascular remodeling and may thereby contribute to plaque stability, or the insulin-like growth factor binding protein 7 (IGFBP7), a cell-cycle arrest marker, which has been linked to ischemic conditions …”
Section: Resultsmentioning
confidence: 99%
“…Other proteins with increased abundance linked to atherosclerosis were the cysteine and glycine-rich protein 2 (CSRP2), which modulates SMC phenotype and thus influences vascular remodeling and may thereby contribute to plaque stability, or the insulin-like growth factor binding protein 7 (IGFBP7), a cell-cycle arrest marker, which has been linked to ischemic conditions …”
Section: Resultsmentioning
confidence: 99%
“…In this research, chronic alcohol treatment led to up‐regulation of Csrp2 , which encodes cysteine‐rich protein 2 (CRP2). Recently, some studies have demonstrated that CRP2 protein, which is responsible for cytoskeleton formation, is widely expressed in vascular smooth muscle cells (VSMCs) and Csrp2 − / − VSMCs exhibited enhancement of cell migration as well as an increase in neointima formation . Another study reported that after vascular injuries that provoke cell proliferation, the expression of CRP2 is decreased in arterial smooth muscle cells of rats .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some studies have demonstrated that CRP2 protein, which is responsible for cytoskeleton formation, is widely expressed in vascular smooth muscle cells (VSMCs) and Csrp2 −/− VSMCs exhibited enhancement of cell migration as well as an increase in neointima formation. 48,49 Another study reported that after vascular injuries that provoke cell proliferation, the expression of CRP2 is decreased in arterial smooth muscle cells of rats. 50 These reports imply that the CRP2 protein negatively affects proliferation of VSMCs and their migration into the intima after arterial injury.…”
Section: Discussionmentioning
confidence: 99%
“…Destrin is responsible for the rapid rearrangement of actin structures in the cells [19], and has been shown to play a crucial role in cell motility [20]. α-skeletal muscle (SM-α) actin is a kind of [21]. Studies reported that the expression of SM-α decreased significantly in VSMCs due to some damage factors caused VSMCs damage [22].…”
Section: Discussionmentioning
confidence: 99%